FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KURANG ENERGI KRONIK (KEK) PADA IBU HAMIL DI WILAYAH KERJA UPTD PUSKESMAS JATILUHUR PURWAKARTA TAHUN 2017 - Rini, Rusmalina Fuspita; Herutomo, Tomi; Haryanto, Irwan (Sekolah Tinggi Ilmu Kesehatan Holistik, 2018)
Background: The high incidence of Chronic Energy Deficiency (CED) in pregnant women in Indonesia could result in risks and complications in pregnant women and children they contain such as maternal anaemia, LOW BIRTH WEIGHT in infants, susceptible to infection, abort, terhambatnya Fetal brain growth and will increase maternal mortality. Purwakarta Regency, Incidence figures in Chronic Energy Deficiency (CED) in pregnant women, one of whom is still high in the area Work UNIT for Clinics Jatiluhur Purwakarta Year 2017 the number of pregnant women BEING BEATEN as many as 74 people or (5.07%). Objective: Describe the factors related to the incidence of Chronic Energy Deficiency (CED) in pregnant women in areas of Work UNIT for Clinics Jatiluhur Purwakarta year 2017. Method: Design research is a cross sectional. The subject is pregnant with Chronic Energy Deficiency (CED) in the working area health centers UNIT for Jatiluhur Purwakarta Year 2017 of 35 people, and the magnitude of the comparison samples of pregnant women do not Work in the area of DOMESTIC VIOLENCE UNIT for Clinics Jatiluhur As many as 35 people so it purwakarta total sample overall as much as 70 people of pregnant women. Data collection using a questionnaire containing questions about total energy, protein intake, smoking habits, alcohol consumption, parity, age, pregnancy, infectious diseases, physical activity, level of education, knowledge, income, and index the time body (IMT). Analysis of test data using the Chi-Square. Result: Factors related to the incidence of chronic less energy is the Total energy of pregnant women (p = 0,004, PR = 0,410), protein intake (p = 0.001, PR = 2,053) that can be said to be two-fold risk of VIOLENCE in pregnant women when the intake of protein ( < 68%), parity (p = 0,024, PR = 0,410), whereas the factors that are not related to VIOLENCE in pregnant women is the distance of pregnancy (p = 0,148, PR = 0,666), age (p = 0,087, PR = 1,6), infectious diseases (p = 0,156, PR = 1,521), level of education (p = 0.000, PR = 0.703), knowledge (p = 0,148, PR = 0,666), and income (p = 0.000, PR = 0,703). Conclusion: There is a relationship between Total energy, Protein intake, and Parity with Chronic Energy Deficiency (CED) in pregnant women.